Biofungicide Activity of Citronella (Cymbopogon nardus L.) and Water Hyacinth (Eichhornia crassipes) Extracts in Inhibiting the Growth of Curvularia lunata - Setyawati, Fani Dewi; Yuliani, Yuliani (LenteraBio : Berkala Ilmiah Biologi, 2023)
Curvularia lunata causes economic losses and health problems. Alternative control of C. lunata with bio-fungicides. Lemon grass and water hyacinth have potential as bio-fungicides because they contain geraniol and flavonoid compounds. The purpose was to determine the antifungal activity of citronella and water hyacinth extracts, the optimal concentration, and their interaction in inhibiting the growth of C. lunata. Types of extracts were citronella, water hyacinth, the combination of them in a ratio of 1:1, 3:1, and 1:3 with concentrations of 20%, 40%, 60%, a positive control of 70% propineb, and a negative control of 10% DMSO. As a result, the type and concentration of the extract affected the growth inhibition of C. lunata. The optimal concentration was at the concentration of 20% citronella extract with a colony diameter of 0,87 ± 0,03 cm and the growth-inhibition percentage of 87,06 ± 0,43%, and there was an interaction with the highest value in the combination of citronella and water hyacinth extracts in ratio 3: 1 concentration of 60% with a colony diameter of 0,80 ± 0,00 cm and growth-inhibition percentage of 88,06 ± 0,00% comparable to propineb. Citronella and water hyacinth extracts can be used as alternative bio-fungicides for synthetic fungicides.